Prediction of The Needs for Benzene Detox with Foods Intake Containing CYP2E1 Enzyme, Sulfation, and Glutathione at Gas Stations Pancoranmas Depok, Indonesia - Abdul Rohim Tualeka1, Pudji Rahmawati2, Ahsan3, Syamsiar S Russeng4, Sukarmin5, Atjo Wahyu6 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Benzene was a dangerous chemical compound which was one of the products of gas stations and one of the chemicals contained in gasoline and it was carcinogenic. TTo reduce and eliminate toxin of benzene from human body, could be used the detoxification process. One of the detoxification process approach was using foods. The aim of this research was to calculate the foods intake containing CYP2E1 enzyme, sulfation, and glutathione to improve benzene detox.Method: The type ofr esearch was descriptive study. The subjects was 15 workers. Location of this research was in gas station Pancoranmas Depok. Variables were body weight, duration of work, working time perweek, working time perday, and benzene concentration. After getting all variables above, breathing rate and intake non-carcinogen per respondent can be calculated. Then, effective doses of foods containing CYP2E1 enzyme, sulfation, and glutathione would be obtained.Results: All respondents were at workplace shows benzene concentration below the TLV. The highest effective dose of foods containing CYP2E1 enzyme was cow brain, sulfation was tuna, and glutathione was carrot.Conclusion: The level of adequacy of enzyme of each respondent was different. Effective dose of each respondent depending on body weight, duration of work, and benzene concentration at workplace. Every respondent could choose foods depending on their needs and taste